Efektivitas Pendidikan Kesehatan dengan Media TB CARD Terhadap Kepatuhan Minum Obat Pasien Tuberkulosis Paru - Tokan, Maria Maresty Patricia; Aty, Yoany Maria V.B.; Gonsalves, Dominggos; Tat, Florentianus (Poltekkes Kemenkes Mataram, 2025)
Background: Tuberculosis is a chronic infectious disease that is still a global health problem, including in Kupang Regency, East Nusa Tenggara. One of the main challenges in TB treatment is the non-compliance of patients taking medication, and the treatment success rate in NTT, which is still below the national target. Health promotion is the key to increasing compliance, one of which is through educational media such as the TB CARD. Objective: To determine the effectiveness of health education with TB CARD media on the medication compliance of pulmonary TB patients in the working area of the Tarus Health Center. Methods: This study used a quasi-experimental design with a non-equivalent control group approach. The sampling technique was simple random sampling with a total of 19 respondents in the intervention group and 19 people in the control group, divided into the intervention group (with TB CARD) and control group (without TB CARD). The data collection instrument used the MMAS-8 questionnaire, and the data analysis used the Wilcoxon and Mann-Whitney tests. Results: Wilcoxon test results showed a significant effect of health education with TB CARD media on increasing compliance with TB medication (p< value 0.05). Conclusion: TB CARD media is effective in increasing medication adherence to pulmonary TB patients in the working area of the Tarus Health Center. Tip: TB CARD can be an alternative educational medium to support the success of TB treatment through increased patient adherence.